Structural identification of neopanaxadiol metabolites in rats by ultraperformance liquid chromatography/quadrupole‐time‐of‐flight mass spectrometry. (15th February 2015) - Geng, Cong; Yin, Jianyuan; Yu, Xiuhua; Yang, Yuxia; Liu, Jingyan; Sun, Dandan; Chen, Fanbo; Wei, Zhonglin; Meng, Qin; Liu, Jihua
<x xml:space="preserve">Abstract</x> RATIONALE Neopanaxadiol (NPD) is one of the major ginsenosides in Panax ginseng C. A. Meyer (Araliaceae) that has been suggested to be a drug candidate against Alzheimer's disease. However, few data are available regarding its metabolism in rats. METHODS In this study, a method of ultraperformance liquid chromatography/quadrupole‐time‐of‐flight mass spectrometry (UPLC/QTOFMS) was developed to identify major metabolites of NPD in the stomach, intestine, urine and feces of rats, with the aim of determining the main metabolic pathways of NPD in rats after oral administration. RESULTS UPLC/QTOFMS revealed two metabolites in the stomach of rats, one metabolite in the intestine and two metabolites in feces. One metabolite, named M2, was isolated and purified from rats feces, which was identified as (20S, 22S)‐dammar‐22, 25‐epoxy‐3β, 12β, 20‐triol based on extensive NMR spectroscopy and mass spectrometry data. The main metabolites of NPD in rats were the products of epoxidation, dehydrogenation and hydroxylation. NPD was predominantly metabolized by 20, 22‐double‐bond epoxidation and rearrangement to yield an expoxidation product (M2). CONCLUSIONS Based on the profiles of the metabolites, possible metabolic pathways of NPD in rats were proposed for the first time. This study provides new and available information on the metabolism of NPD, which is indispensable for further research on metabolic pathways of dammarane ginsengenins in vivo. Copyright © 2014 John Wiley & Sons, Ltd.